2018
DOI: 10.1016/j.amsu.2018.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Atypical angiofibroma in a patient with compromised general health: A case report

Abstract: IntroductionThe nasopharyngeal angiofibroma (NA) is a benign tumor that originates from the pterygopalatine fossa and extends to the adjacent anatomical structures and affects frequently young individuals. The basic treatment for NA is surgical resection, but in some cases the tumor is surgically inaccessible.Case presentationWe describe the case of a 45-year-old male with respiratory difficulty after the appearance of a soft palate lesion. The clinical appearance of NA was not specific.DiscussionThere are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Celik et al presented four atypical cases of angiofibroma with unusual localization of the tumor like tonsillar bed or inferior concha [ 4 ]. Vasconcelos AC et al reported an atypical angiofibroma with a soft palate lesion [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Celik et al presented four atypical cases of angiofibroma with unusual localization of the tumor like tonsillar bed or inferior concha [ 4 ]. Vasconcelos AC et al reported an atypical angiofibroma with a soft palate lesion [ 7 ].…”
Section: Discussionmentioning
confidence: 99%